In vitro two-dimensional and three-dimensional tenocyte culture for tendon tissue engineering. - Qiu, Y; Wang, X; Zhang, Y; Carr, A; Zhu, L; Xia, Z; Sabokbar, A (John Wiley and Sons, Ltd, 2013)
In order to examine the differentiation potential of the tenocytes expanded in our defined culture medium (reported previously) and the effect of sequential combination of the two culture conditions on human tenocytes, a two-dimensional and three-dimensional experimental approach was used. Human tenocytes were sequentially exposed to 1% fetal bovine serum (FBS) + 50 ng/ml platelet-derived growth factor-BB (PDGFBB ) + 50 ng/ml basic fibroblast growth factor (bFGF) for the first 14 days (expansion phase) followed by a further 14-day culture in the presence of 10 ng/ml transforming growth factor β-3 plus 50 ng/ml insulin-like growth factor 1, but in the absence of serum (differentiation phase). The results showed that by sequential treatment of human tenocytes maintaining a long-term two-dimensional tenocyte culture in vitro for up to 28 days was possible. These findings were further verified using a three-dimensional scaffold (Bombyx silk) whereby the tendon-like constructs formed resembled macroscopically and microscopically the constructs formed in 10% FBS supplemented culture media and the human hamstring tendon. These findings were further substantiated using haematoxylin and eosin staining, scanning electron microscopy and by immunohistochemical detection of type I collagen. In addition, the mechanical properties of the three-dimensional constructs were determined to be significantly superior to that of the natural human hamstring tendon. This is the first report to demonstrate a possible approach in expanding and differentiating human tenocytes for tendon tissue engineering. Copyright © 2013 John Wiley and Sons, Ltd.